Optimasi Penjadwalan Perawat IGD RSUD Arosuka dengan Metode 0-1 Fuzzy Goal Programming - Intan Ayu Ramadhani; Yusmet Rizal (UNIVERSITAS NEGERI PADANG, 2023)
Nurse scheduling problem is an important aspect in maintaining the quality of hospital services. The fact that the number of patients is greater than the limited number of nurses and there are rules from the hospital that must be complied with makes the nurse scheduling problem more complex. The purpose of this study was to the shape of the model and the results of optimizing the scheduling of emergency room nurses at Arosuka Hospital using the method 0-1 Fuzzy Goal Programming. Model 0-1 Fuzzy Goal Programming is the result of the application of set theory Fuzzy on Goal Programming that uses a decision variable of 0 or 1. By completing the scheduling model with help LINGO 20.0 software, the results show that with the methodl 0-1 Fuzzy Goal Programming has fulfilled all existing constraints, and can maximize all objectives. In the manual schedule there are sixty one activities which not corresponding with the policy, while with the 0-1 Fuzzy Goal Programming model it has been minimized so that there are only thirty three activities which not corresponding with the policy.